1996
DOI: 10.1177/095632029600700508
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis B Virus Replication by Nucleoside Enantiomers of β-2′,3′-Dideoxypurine Analogues

Abstract: Various purine β-L-2′,3′-dideoxynucleoside analogues with both sugar and base modifications including β-L-ddG, β-L-ddl, β-L-ddA, 2′-azido-β-L-araddA, 2′-amino-β-L-araddA, 2′,5′-anhydro-β-L-araddA, 2′-azido-β-L-ddA, 2′-amino-β-L-ddA, 2′-fluoro-β-L-ddA, 3′-azido-β-L-ddA, 3′-amino-β-L-ddA, 3′-fluoro-β-L-ddA, 2,6-diamino-β-L-2′,3′-dideoxyfuranosylpurine, 6-cyclopropylamino-β-L-ddA, 2′-azido-6-N-triphenylphosphine-β-L-araddA, 2-amino-6-methylamino-β-L-2′,3′-dideoxyfuranosylpurine, 2-amino-6-cyclopropylamino-β-L-2′,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Finally, the rate of ␤-L-ddA catabolism can explain its differential antiviral activity against HIV (EC 50 , Ͼ100 M) grown in PBMC (1) and HBV (EC 50 , 5 to 6 M) grown in HepG2 cells (4,8). In PBMC, the metabolites resulting from [ 3 H]␤-LddA catabolism accounted for over 90% of the intracellular radioactivity (Table 2), while in HepG2 cells these metabolites accounted for only 40% of the total radioactivity (Table 1).…”
Section: Coincubation Of [ 3 H]␤-l-dda and Mta In Hepatocytes In Cultmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the rate of ␤-L-ddA catabolism can explain its differential antiviral activity against HIV (EC 50 , Ͼ100 M) grown in PBMC (1) and HBV (EC 50 , 5 to 6 M) grown in HepG2 cells (4,8). In PBMC, the metabolites resulting from [ 3 H]␤-LddA catabolism accounted for over 90% of the intracellular radioactivity (Table 2), while in HepG2 cells these metabolites accounted for only 40% of the total radioactivity (Table 1).…”
Section: Coincubation Of [ 3 H]␤-l-dda and Mta In Hepatocytes In Cultmentioning
confidence: 99%
“…135, 1998). However, ␤-L-ddA per se has a limited anti-HBV activity (50% effective concentration [EC 50 ], 5 to 6 M) in HBV DNA-transfected human hepatoblastoma-derived HepG2 cells (2.2.15 cells) and no anti-HIV activity (EC 50 , Ͼ100 M) in peripheral blood mononuclear cells (PBMC) (1,4,8,10). Previous studies showed that ␤-L-ddA is phosphorylated by 2Ј-deoxycytidine kinase (EC 2.7.1.74) with a high K m of 220 M (6).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that β-L-ddA lacked potent anti-HIV and anti-HBV activity in PBMCs and in 2.2.15 cells (Bolon et al, 1996;El Alaoui et al, 1996). The poor antiviral activity of β-L-ddA was attributed to a rapid and extensive catabolism of the drug by 5′-methylthioadenosine phosphorylase (EC 2.4.2.28).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside analogues have been a point of interest for chemists and biochemists due to their role in nucleic acid biosynthesis and various other biologically significant processes such as viral replication and division of cells. 1 In the past few decades, a variety of artificial or modified nucleosides have been synthesized by chemists to incorporate them in the antisense oligonucleotides [2][3][4] or to screen their biological activities such as antiviral, 5,6 anti-HIV, 7,8 anticancer, 9,10 antimetabolites, 11,12 antisense properties, 13 and many more. [14][15][16] Conformationally restricted nucleoside analogues with reduced conformational flexibility constituted a major class of these modified nucleosides.…”
mentioning
confidence: 99%